Putting(us) in common: Production of knowledge and narratives in/from social work. - Duboy Luengo, Mitzi; Duarte Hidalgo, Cory; Hernández Mary, Natalia (Critical Proposals in Social Work, 2023)
The article exposes a reflective exercise, in which, starting from recognizing ourselves and weaving (us) in common, we propose to carry out a disciplinary questioning of the methodological processes deployed in the production of knowledge, associated with the question of how we do what we do. For this, the need to expand and move the margins arises, leaving the presumption regarding the objectivity of a model of knowledge that claims a single truth. In this way, it seeks to accommodate other views around the approaches and conceptions of knowledge as alternatives to those contained in the neoliberal ethos, inserted in a hegemonic, male-centered, binary, patriarchal and colonial model. From there, power relations are reviewed, how these are articulated and intersect with the logics of knowledge production in the Social Sciences in general and in social work in particular, questioning the academic production and the usual practices of knowledge to which the discipline. In this sense, elements associated with geo- and corpo-politically situated positions are reviewed, in a continuous exercise of resistance, intertwining social work with feminist practices and theories. From that place of enunciation, we propose the use of Narrative Productions as a methodological strategy from feminist research, whose main value is that it allows us to weave together, generating processes of co-labor, revealing the possibility of stressing power relations. that are established in the investigative processes, deconstructing naturalized spaces, and integrating affective and collaborative elements.